Larger Interventricular Conduction Time Enhances Mechanical Response to Resynchronization Therapy. Issue 4 (10th January 2013) - PADELETTI, LUIGI; PIERAGNOLI, PAOLO; RICCIARDI, GIUSEPPE; PERROTTA, LAURA; PERINI, ALESSANDRO P.; GRIFONI, GINO; RICCERI, ILARIA; PADELETTI, MARGHERITA; LIONETTI, VINCENZO; VALSECCHI, SERGIO
<x xml:space="preserve">Abstract</x> Background Previous studies have reported that the left ventricular (LV) pacing site is a major determinant of the hemodynamic response to cardiac resynchronization therapy (CRT). However, lead positioning in a lateral or posterolateral cardiac vein may not be optimal for every patient. The objective of this study was to assess the relationship between the right ventricular (RV)‐to‐LV conduction time and the systolic function during CRT on the basis of changes to LV pressure‐volume loops. Methods Left ventricular pressure and volume data were determined using a conductance catheter during CRT device implantation in 10 patients. Four endocardial LV sites were systematically assessed at four atrioventricular delays. The RV‐to‐LV conduction time was measured as the time interval between spontaneous peak R waves, recorded through the RV lead and the LV catheter. Results The optimal pacing site varied among patients. However, the pacing site associated with the maximum RV‐to‐LV conduction time resulted in a stroke volume improvement comparable to the pacing site identified through individual hemodynamic optimization (41 ± 17 mL vs 44 ± 18 mL, P = 0.266). Moreover, the RV‐to‐LV conduction time recorded at each endocardial pacing site correlated positively with the increase in stroke volume (r = 0.537; P < 0.001), stroke work (r = 0.642; P < 0.001), and the pressure‐derivative maximum (r = 0.646; P < 0.001) obtained with CRT. Conclusions An optimal acute response to CRT can be obtained by positioning the LV lead at the site associated with the maximum RV‐to‐LV conduction time. A significant correlation appears to exist between RV‐to‐LV conduction time and the improvement in systolic function with CRT.